IT TAKES TWO TO TANGO: potential novel therapies for autosomal dominant optic atrophy - Sampige, Ritu; Seaborn, Lyra E.A.; Pluenneke, Molly; Jyothi, Annika; Saland, Sophie; Chinedu-Obi, Chisom M.; Keehn, Caroline; Lee, Andrew G. (Frontiers in Ophthalmology, 2025)
Autosomal dominant optic atrophy (ADOA) is among the most prevalent inherited optic neuropathies with hallmark symptoms of bilateral, painless, progressive, and typically permanent vision loss over time. ADOA can affect patients’ quality of life with debilitating visual symptoms, and there is a pressing need for effective therapeutics. In this paper, we review the current and future investigational therapies for ADOA, including the use of intravitreal injections of antisense oligonucleotides through Targeted Augmentation of Nuclear Gene Output (TANGO), CRISPR-based therapy, genetic editing, gene replacement approaches, and idebenone, a small-molecule mitochondrial modulator. Additionally, we review clinical trials for ADOA treatment and opportunities for future research on ADOA therapeutics, including the utilization of mitochondria-targeted peptides and antioxidants, NAD+ boosters/metabolic support, mitophagy and fission-fusion modulators, and cell-based regenerative therapy. The use of emerging technology to compensate for OPA1 protein haploinsufficiency provides new and vast avenues for the management of this otherwise vision-altering disease. Increased awareness of therapeutics for ADOA will allow for patient counseling regarding treatment access via clinical trials and for underscoring the importance of genetically testing family members, who may be incidentally identified with ADOA in a timely manner for newly available therapies. While patients with ADOA typically have poor visual prognoses, there are increasing promising therapies with the potential for preserving and improving visual function.